‘Tightness’, autonomy and release: The anticipated pains of release and life licencing - Rennie, Ailie (The British journal of criminology, 2023)
This article explores how men serving mandatory life sentences in England and Wales anticipate life after release and the imposition of a life licence. It reports the various ways that lifers feared licencing as being exceedingly ‘tight’ and restrictive, sometimes resulting in them retreating from release altogether. At the same time, some participants reported a motivation to embrace the ‘tightness’ of their impending licence conditions, and use penal power as a means of structuring life on release. Whether they resisted or embraced penal intervention, all participants altered their aspirations to what seemed achievable upon release when subject to numerous conditions. Specifically, the article argues that the anticipation of a particular mode of penal power has a material effect on lifers’ approach to release.